2019
DOI: 10.1021/acs.jpcc.9b04080
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Carbon Dioxide on Au Nanoparticles: An in Situ FTIR Study

Abstract: For the conversion and storage of renewable energy, the electrochemical reduction of CO2 to hydrocarbon fuels and chemicals comprises one of the most promising strategies. A number of studies have focused on the development of robust electrocatalysts for the reduction of CO2 with high efficiency and selectivity. Most of the proposed mechanisms of the CO2 reduction are based primarily on theoretical calculations. Although a few studies have been dedicated to the in situ direct detection of intermediates, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…It has been reported that Au NPs in size of more than 8 nm exhibit a low current density . Our results are comparable to the reported current density of 0.35 mA cm −2 at −0.5 V for Au NPs with an average size of more than 20 nm and −1.3 mA cm −2 at −0.7 V for Au NPs with an average size of more than 9 nm . It further evidences the critical role of PANI in the AU−PANI composite for CO 2 reduction.…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that Au NPs in size of more than 8 nm exhibit a low current density . Our results are comparable to the reported current density of 0.35 mA cm −2 at −0.5 V for Au NPs with an average size of more than 20 nm and −1.3 mA cm −2 at −0.7 V for Au NPs with an average size of more than 9 nm . It further evidences the critical role of PANI in the AU−PANI composite for CO 2 reduction.…”
Section: Resultssupporting
confidence: 90%
“…[27] This COOH species intensified with light irradiation, which has been identified as a key intermediate in the production of CO. [8] Besides, a peak due to OH bending (1655 cm −1 ) remained prominent throughout the reaction. [28] Taken collectively, the DRIFT data provide strong evidence that during the photoreduction of CO 2 over Ni-SA-5/ZrO 2 , adsorbed CO 2 is converted to a COOH intermediate, with O COH bond scission then yielding CO and a surface OH group. Finally, temperature programmed desorption of CO (CO-TPD) over the various photocatalysts was studied ( Figure S23, Supporting Information).…”
Section: % Selectivity) Experimental and Theoretical Investigationsmentioning
confidence: 66%
“…In electrochemical energy storage and conversion devices, as well as in electrochemical synthesis, noble metals are widely used catalysts in the form of nanoparticles (NPs) dispersed on high area carbon supports. For example, Pt NPs are a state-of-the-art catalyst for several reactions, such as oxygen reduction and hydrogen oxidation/evolution; 1 3 Ir-oxide and Ru-oxide are the best catalysts for oxygen evolution, 4 , 5 while Au is used for electrochemical CO 2 reduction 6 8 and H 2 O 2 production through selective 2e – oxygen reduction reaction. 8 12 Besides activity, a suitable catalyst must provide long term durability and stable running of the given electrochemical process to fulfill the basic demands for commercial applicability, so it is necessary to understand electrochemically induced dissolution and other structural changes of noble metals.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 34 Interestingly, in the case of Au NPs, there is a lack of AST in the literature even though Au NPs are widely used in electrocatalysis. 6 12 They can also be applicable in fuel cells since the addition of gold increases the stability of Pt during oxygen reduction. 39 41 With that in mind, the AST performed solely for Au NPs would provide a benchmark and shed some light on their long-term stability and possible usage as durable electrocatalysts, for instance, for hydrogen peroxide production or carbon dioxide reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation